2007
DOI: 10.1002/art.22372
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for uncoupling of inflammation and joint remodeling in a mouse model of spondylarthritis

Abstract: Objective. To study the relationship between inflammation and remodeling by inhibiting tumor necrosis factor ␣ (TNF␣) in male DBA/1 mice with spontaneous arthritis, a model of spondylarthritis (SpA).Methods. TNF␣ was inhibited using etanercept, a soluble TNF receptor. The efficacy of the dose used (25 g/mouse) was confirmed in methylated bovine serum albumin (mBSA)-induced monarthritis, a model of inflammation-driven joint destruction. Male DBA/1 mice with spontaneous arthritis were caged together from the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
107
3
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(125 citation statements)
references
References 54 publications
(76 reference statements)
9
107
3
6
Order By: Relevance
“…This research has not provided convincing evidence of slowing of radiographic progression, despite anti-TNF treatment for up to 4 years. Explanatory theories suggest that inflammation and bony progression are 2 independent pathways, and that suppression of inflammation may not prevent spinal ankylosis (34). The impact of TNF blockade on new bone formation in the spine has been controversial, and it has been suggested that once inflammation has started, the bony progression cannot be halted with suppression of TNF alone.…”
Section: Discussionmentioning
confidence: 99%
“…This research has not provided convincing evidence of slowing of radiographic progression, despite anti-TNF treatment for up to 4 years. Explanatory theories suggest that inflammation and bony progression are 2 independent pathways, and that suppression of inflammation may not prevent spinal ankylosis (34). The impact of TNF blockade on new bone formation in the spine has been controversial, and it has been suggested that once inflammation has started, the bony progression cannot be halted with suppression of TNF alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from animal models of spondylarthritis (SpA), principally ankylosing enthesitis, directly challenged this hypothesis by demonstrating that anti-tumor necrosis factor ␣ (anti-TNF␣) therapy did not prevent the development of ankylosis (1). An alternative hypothesis was then proposed whereby pathogenetic factors such as altered gene expression, biomechanical factors, and bacteria trigger the concomitant expression of inflammation and new bone formation, which then proceed along essentially autonomous pathways (2).…”
mentioning
confidence: 99%
“…The Luyten's group has characterized the spondyloarthropathy-like arthritis that spontaneously develops in aging DBA/1 mice. 2,3 In this mouse model, new bone formation starts at the enthesis and occurs through endochondral ossification. 2 On the other hand, Benjamin and McGonagle have thoroughly studied the age-related enthesophyte formation in the Achilles tendon in both rodents and humans.…”
mentioning
confidence: 99%
“…10 Moreover, although anti-tumor necrosis factor a (anti-TNF-a) therapies have been shown to improve most symptoms in AS patients, they have proven unsuccessful to block the progression of bone spurs both in patients with AS, 7,10 and in the DBA/1 model of spondyloarthropathy. 3 The fact that anti-TNF treatments do not significantly alter the course of syndesmophyte formation may be due to the fact that TNF-a likely displays both stimulatory and inhibitory effects, as it does in endochondral ossification during bone healing. [11][12][13] It is also possible that other cytokines are involved in syndesmophyte formation.…”
mentioning
confidence: 99%